Social capital of the community in the management of Danau Sentarum National Park, West Kalimantan, Indonesia - EMI ROSLINDA (Biodiversitas Journal of Biological Diversity, 2018)
Roslinda E. 2018. Social capital of the community in the management of Danau Sentarum National Park, West Kalimantan, Indonesia. Biodiversitas 19: 1249-1257. Many studies on the management of National Park have been conducted in various countries. This research highlights the management of Danau Sentarum National Park which is administratively located in West Kalimantan Province precisely in Kapuas Hulu District, from the view of social capital. The research method was surveyed using a quantitative approach. Social capital of the community in the area of Danau Sentarum National Park is still high/strong. Based on this fact, the management of the National Park that has been conducted by the government alone can collaborate with the management by community and collaborative management that pays a good attention to the minimum resistance and maximum synergy.